Design-oriented evaluation of the hydrodynamics in a full-scale combined filter-lamella separator for urban stormwater treatment. (21st April 2022) - Stricker, Max; Littfinski, Tobias; Heinz, Eva; Pecher, Klaus Hans; Lübken, Manfred; Grüning, Helmut; Wichern, Marc
Abstract: The development of compact treatment devices with high removal efficiencies and low space requirements is a key objective of urban stormwater treatment. Thus, many devices utilize a combination of sedimentation and upward flow filtration in a single system. This study, for the first time, evaluates the flow field inside a combined filter-lamella separator via computational fluid dynamics. Herein, three objectives are investigated: (i) the flow field for different structural configurations, (ii) the distribution of particulate matter along the filter bed and (iii) the dynamic clogging in discrete filter zones, which is addressed by a clogging model derived from literature data. The results indicate that a direct combination of a filtration stage with a lamella separator promotes a uniform flow distribution. The distribution of particulate matter along the filter bed varies with configuration and particle size. Clogging, induced by particles in the spectrum <63 μm, creates gradients of hydraulic conductivity along the filter bed. After treating about half of Germany's annual runoff-efficient precipitation at a rainfall intensity of 5 L/(s·ha), the filtration rates increase in the front of the filter bed by +10%. Thus, long-term operating behavior is sensitive to efficient filter utilization in compact treatment devices. HIGHLIGHTS A holistic approach is used to capture the system behavior concerning hydrodynamics, filter resistance and filter clogging. The filter media improves the distribution of flow in the lamella stage. Larger particles utilize only about 50% of the filter area due to inertia effects. Gradients of hydraulic conductivity regionally alter filtration rates and flow rates in the inclined plates. Graphical Abstract